Silicon nanoparticles (SiNPs) restore photosynthesis and essential oil content by upgrading enzymatic antioxidant metabolism in lemongrass (Cymbopogon flexuosus) under salt stress - Mukarram, Mohammad; Khan, M. Masroor A.; Kurjak, Daniel; Lux, Alexander; Corpas, Francisco J. (Frontiers in Plant Science, 2023)
Lemongrass (Cymbopogon flexuosus) has great relevance considering the substantial commercial potential of its essential oil. Nevertheless, the increasing soil salinity poses an imminent threat to lemongrass cultivation given its moderate salt-sensitivity. For this, we used silicon nanoparticles (SiNPs) to stimulate salt tolerance in lemongrass considering SiNPs special relevance to stress settings. Five foliar sprays of SiNPs 150 mg L-1 were applied weekly to NaCl 160 and 240 mM-stressed plants. The data indicated that SiNPs minimised oxidative stress markers (lipid peroxidation, H2O2 content) while triggering a general activation of growth, photosynthetic performance, enzymatic antioxidant system including superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD), and osmolyte proline (PRO). SiNPs amplified stomatal conductance and photosynthetic CO2 assimilation rate by about 24% and 21% in NaCl 160 mM-stressed plants. Associated benefits contributed to pronounced plant phenotype over their stressed counterparts, as we found. Foliar SiNPs sprays assuaged plant height by 30% and 64%, dry weight by 31% and 59%, and leaf area by 31% and 50% under NaCl 160 and 240 mM concentrations, respectively. SiNPs relieved enzymatic antioxidants (SOD, CAT, POD) and osmolyte (PRO) in lemongrass plants stressed with NaCl 160 mM (9%, 11%, 9%, and 12%, respectively) and NaCl 240 mM (13%, 18%, 15%, and 23%, respectively). The same treatment supported the oil biosynthesis improving essential oil content by 22% and 44% during 160 and 240 mM salt stress, respectively. We found SiNPs can completely overcome NaCl 160 mM stress while significantly palliating NaCl 240 mM stress. Thus, we propose that SiNPs can be a useful biotechnological tool to palliate salinity stress in lemongrass and related crops.